What Can Trigger Spontaneous Regression of Breast Cancer? - Nicoletta D’Alessandris; Angela Santoro; Damiano Arciuolo; Giuseppe Angelico; Michele Valente; Giulia Scaglione; Stefania Sfregola; Angela Carlino; Elena Navarra; Antonino Mulè; Gian Franco Zannoni (Diagnostics, 2023)
Background: Spontaneous regression of tumors is a rare phenomenon in which cancer volume is reduced or, alternatively, a tumor completely disappears in the absence of any pharmacological treatment. This phenomenon has previously been described in several tumors, such as neuroblastomas, testicular malignancies, renal cell carcinomas, melanomas, and lymphomas. Spontaneous remission has also been documented in breast cancer; however, it represents an extremely rare and poorly understood phenomenon, with only a few reported cases in the literature. Methods: We herein report two cases of breast cancer that showed spontaneous tumor regression in the surgical specimen after a pathologically confirmed diagnosis of invasive breast cancer in core needle biopsy samples. Results: Macroscopically, both the surgical samples revealed a whitish, fibrous area with a rubbery consistency. On histological examination, diffuse fibrous tissue, hemosiderin deposition, and chronic inflammation were observed. The first case showed the complete disappearance of the tumor, whereas the second case showed just a small (3 mm), residual nest of neoplastic cells. Conclusions: Although spontaneous regression of breast cancer is a rare event, it is important to know that it might happen. It is also of great importance to try to better explain, over time, its underlying mechanism. This knowledge could help us to further develop cancer prevention methods and predict the clinical course of these kinds of neoplasms.